Inkonsistensi Terhadap Pengakuan Desa Adat Dalam Undang-undang Nomor 6 Tahun 2014 tentang Desa (RechtJiva, 2024)
The Village Law was supposed to be a breath of fresh air for villages across Indonesia that still have customs or customary laws, as they can use their own customary government format with various provisions. However, administrative constraints become a restraint in the process of determining villages to become customary villages. Based on these problems, the formulation of the problem in this research is: How is the relationship between the boundaries of an indigenous village and the process of establishing an indigenous village? And how is the ideal reformulation in the determination of indigenous villages? This research method uses normative juridical research with statutory and conceptual approaches. This research results in two conclusions: first, that the existence of customary villages cannot be separated from the existence of customary law communities. This is reflected in the requirements of customary villages in the Village Law. However, there is a problem, namely the provision of time limits in the process of determining customary villages. Second, in essence, the elimination of the 1 (one) year period is a form of respect for the constitutional rights of indigenous peoples.